MENINGKATKAN HASIL BELAJAR SENI BUDAYA DAN KETERAMPILAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PBL) SISWA KELAS V MIN SIBUHUAN - Hasibuan, Sutan Botung; Rizki Hamdan Saputra; Hasibuan, Alwi Hamdan; Pulungan, Leni Herawati (Journal Education Innovation (JEI), 2025)
Based on the research results, it can be concluded that: (1) The learning outcomes of art, culture and skills of Class V MIN Sibuhuan students before using the Project Based Learning (PBL) learning model, namely in the pre-cycle only 7 students achieved the KKM with a percentage of 25.00% and 21 students scored below the KKM with a percentage of 75.00%. So it can be seen that learning in the pre-cycle is still low. (2) Improvement in learning outcomes of art, culture and skills by using the Project Based Learning (PBL) learning model of Class V MIN Sibuhuan students in cycle I out of 28 students, there were 16 students who achieved the KKM with a percentage of 57.14% who were able to achieve the KKM. While 12 students or 42.86% whose scores were still below the specified KKM, and in cycle II there were 25 students or 89.29% who were able to achieve the KKM. While 3 students or 10.71% whose scores were still below the specified KKM. The percentage of student learning outcomes in the subject of art and culture after using Project Based Learning (PBL) has reached the success indicator, namely 85% of all students who have completed their studies. So it can be concluded that the implementation of the Project Based Learning (PBL) learning model can improve the learning outcomes of art and culture and the skills of class V students of MIN Sibuhuan.